PENGARUH BRANDING LAYANAN KESEHATAN TERHADAP CITRA INSTITUSI DAN KEPUTUSAN PASIEN - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2026)
This study examines the influence of healthcare branding on institutional image and patient decision-making. Branding in the healthcare sector is a key strategy for healthcare institutions to build their identity, enhance trust, and create a positive perception amongst the public. A positive institutional image strengthens the reputation of healthcare services, whilst patients’ decisions regarding service selection are significantly influenced by their perceptions of quality, credibility and experience, which are shaped through branding. This study employs a literature review method, examining various relevant academic sources, such as books, journal articles, and previous research findings. The results of the review indicate that healthcare service branding plays a vital role in shaping a positive institutional image and significantly influences patient decision-making. Therefore, consistent branding management that is oriented towards patient needs is a strategic factor in enhancing the competitiveness of healthcare institutions.